2018
DOI: 10.1136/bjophthalmol-2018-312972
|View full text |Cite
|
Sign up to set email alerts
|

Success of trabeculectomy surgery in relation to cataract surgery: 5-year outcomes

Abstract: AimsTo compare success proportions at 5 years in three surgical groups: group 1, trabeculectomy alone; group 2, trabeculectomy followed by cataract surgery within 2 years; and group 3, trabeculectomy performed on a pseudophakic eye.MethodsA retrospective cohort study. 194 eyes of 194 patients were identified with at least 5 years’ follow-up post trabeculectomy (N=85, 60 and 49 in groups 1, 2 and 3, respectively).Main outcome measures1. Primary outcome measure: intraocular pressure (IOP) at 5 years post-trabecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
(11 reference statements)
0
16
0
2
Order By: Relevance
“…It has been well described that cataract surgery in patients with glaucoma is more complex than the routine phacoemulsification. Moreover it is still widely thought that cataract surgery following trabeculectomy will increase the risk of bleb failure [ 40 ] in spite of studies claiming otherwise [ 40 , 41 ]. In fact some surgeons went as far as using cataract surgery in an attempt to treat postoperative hypotony and its complications with good success [ 42 ].…”
Section: Surgical Considerations In Patients With Past Trabeculectomymentioning
confidence: 99%
“…It has been well described that cataract surgery in patients with glaucoma is more complex than the routine phacoemulsification. Moreover it is still widely thought that cataract surgery following trabeculectomy will increase the risk of bleb failure [ 40 ] in spite of studies claiming otherwise [ 40 , 41 ]. In fact some surgeons went as far as using cataract surgery in an attempt to treat postoperative hypotony and its complications with good success [ 42 ].…”
Section: Surgical Considerations In Patients With Past Trabeculectomymentioning
confidence: 99%
“…8 The strictest target IOP reported on most studies is an IOP ≤18mmHg. 2,6 However, we considered that in patients with advanced glaucoma, the aim should be to obtain lower IOP levels. The Advanced Glaucoma Intervention Study (AGIS) reported that an IOP at which visual field loss stabilizes in an average of 12.3 mmHg, also recommending target reductions from baseline of 40% in severe cases or 30% in moderate ones.…”
Section: Definitions Of Success Qualified Success and Failurementioning
confidence: 99%
“…When affected by both conditions, the surgical approach is widely debated, with several advocating to undertake procedures in a specific order and many others favor performing both simultaneously. 2,3,4,5 The gold standard of combined procedures is phacoemulsification + trabeculectomy. However, in low income populations this type of surgery has certain disadvantages mainly derived from its cost and follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…La PIO meta más estricta informada en la mayoría de los estudios es ≤ 18 mmHg 2,6 . Sin embargo, consideramos que en los pacientes con glaucoma avanzado el objetivo debe ser obtener unos valores de PIO más bajos.…”
Section: Definiciones De éXito éXito Calificado Y Fracasounclassified
“…El tratamiento de las cataratas es quirúrgico, mientras que el del glaucoma puede ser médico, con láser o quirúrgico, según la gravedad. Cuando existen ambas condiciones, el abordaje quirúrgico es ampliamente debatido, con varios autores que abogan por realizar los procedimientos en un orden específico y muchos otros que favorecen la realización de ambos de manera simultánea [2][3][4][5] .…”
Section: Introductionunclassified